HIMENÓPTEROS PARASITOIDES (CHALCIDOIDEA) DE COCCOIDEA (HOMOPTERA) EN CD. VICTORIA, TAMAULIPAS, MÉXICO - Gaona García, Griselda; Ruíz Cancino, Enrique; Myartseva, Svetlana N.; Trjapitzin, Vladimir A.; Coronado Blanco, Juana María; Mora Olivo, Arturo (Instituto de Ecología, A.C., 2006)
Collectings of Coccoidea on ornamentals plants, fruit trees and shadow trees were done in 25 localities of Ciudad Victoria, Tamaulipas, Mexico, from April 1998 to September 2001, obtaining 32 parasitoid species of the families Aphelinidae, Encyrtidae, Eulophidae and Signiphoridae, emerged from 24 species of Coccoidea.